2013
DOI: 10.1080/21507686.2012.722553
|View full text |Cite
|
Sign up to set email alerts
|

School-based cognitive-behavioural therapy for academically underachieving Singaporean adolescents with aggressive and rule-breaking behaviour

Abstract: This study examined the utility of a school-based, cognitive-behavioural therapy (CBT) programme for academically weak adolescents with at-risk levels of aggressive and rule-breaking tendencies. When compared to baseline data, standardized self-report and teacher rating scales revealed that the symptoms of the CBT group significantly reduced to within normal limits at post-treatment. These gains were also evident at 1-month post-treatment. In contrast, the aggressive and rule-breaking behaviour of the wait-lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We identified 24 articles that evaluated the impact on academic outcomes of targeted prevention components of school behavioral health programs or frameworks . A table containing summary information about the articles is available as Table S2 (also at http://csmh.umaryland.edu/Resources/School-Mental-Health-Impact/).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 24 articles that evaluated the impact on academic outcomes of targeted prevention components of school behavioral health programs or frameworks . A table containing summary information about the articles is available as Table S2 (also at http://csmh.umaryland.edu/Resources/School-Mental-Health-Impact/).…”
Section: Resultsmentioning
confidence: 99%
“…CBT interventions have often been found to be effective for both male and female offenders (Lipsey, 2009). In addition, some evidence has suggested that CBT may be effective for adolescents with various ethnic backgrounds (Krishnan, Yeo, & Cheng, 2013;Lipsey, 2009), but research has been limited. In general, most studies have been conducted in North America and Europe and have consisted mainly of Caucasian and African American participants.…”
Section: Approaches That Target the Individual Youthmentioning
confidence: 99%